The Challenge of Nation-Building in a Geopolitically Contested Region. - BRANDT, CARMEN (Asian Ethnology, 2021)
The Baltis mostly inhabit a region at the western edge of the Himalayas, also known as Baltistan. Today, Baltistan is considered to be a geographic and geopolitical border region; it is administered predominantly by Pakistan and claimed as a whole by India. Moreover, the Balti language is associated with a third entity, Tibet, while the fact that Baltis identify as Muslims, the majority Shiites, and hence consider Iran a friendly state, adds another dimension to the intricacy of their multiple belongings. Drawing on research in Baltistan in 2014 and 2017, particularly qualitative interviews with Baltis of various backgrounds, this article will show that the current endeavors to standardize a script--a variant of the Perso-Arabic, Tibetan, or Roman scripts--for the currently only sparsely written Balti language illustrate the struggle of identity formation and nation-building among Baltis during the early twenty-first century.